Bio-decolorization of Direct Textile Dyes by Aspergillus Isolates Producing Denim Bio-stoning Cellulase - Taslim, Asma Ul; Hakim, Al; Abul Kalam , Azad (Bangladesh Journal of Microbiology, 2025)
Microbial cellulase is represented as biocatalysts due to their widespread applications in textile industries. As the cellulase from four fungal isolates can perform bio-stoning of denim fabrics, this enzyme may have the capability for the decolorization of textile dyes. This study evaluated the decolorization potential of four Aspergillus isolates, A. fumigatus AKAL1, A. oryzae AKAL4, A. flavus AKAL8, and A. flavus AKAL9, along with their crude cellulases. The crude cellulase having denim bio-stoning capability demonstrated decolorization of direct textile dyes, Dark Blue GL and Black VSF, with maximum decolorization percentages ranging from 50%-55% for both dyes. The fungal isolates effectively decolorized two commercial textile dyes. The maximum decolorization was achieved under static conditions. The optimal parameters for decolorization by the isolates were identified as 0.01% dye concentration, pH 7.0 for Dark Blue GL, pH 5.0 for Black VSF, incubation at 30°C for seven days, and dextrose as the carbon source. Results indicate that the four fungal isolates obtained in this study might be a potential source for textile dye decolorization. Bangla. J. Microbiol. 2025, Vol. 41, P: 1-8